Media and Cybersecurity: Representation of Cybercrime in the Serbian Digital Space - Bogićević, Aleksandar (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2026)
Relying on the application of framing theory, a content analysis was conducted on 222 news articles published between February 2022 and February 2025 on three online platforms: RTS (the national public broadcaster), Kurir (tabloid daily), and Danas  (a critically oriented media outlet). The articles were coded according to thematic focus, geographic scope, information sources, presence of educational content, and dominant journalistic frames. The study aims to examine how Serbian media construct representations of cybercrime and to what extent these representations may contribute to either the education or the misinformation of the public regarding this important issue. The findings indicate that cybercrime is most frequently framed through conflict and responsibility attribution, with particular emphasis on inter-state cyberattacks in the context of the conflict in Ukraine. Domestic cases, however, are often portrayed as technical incidents of limited political significance. It is important to note that, although educational content aimed at raising individual awareness of cyber security is present, it is often overshadowed by alarmist and simplified reporting. The study concludes that, despite recognising the growing significance of cyber threats, the observed Serbian media have not yet fully adapted their reporting to the complexities of cybercrime. The preference for sensationalism and institutional narratives over critical engagement may lead to a distorted public perception of cyber security. Nevertheless, the identified presence of preventive and educational messages highlights the potential of the media as a significant component of societal resilience in the digital age.
Keywords: Cybercrime; Media discourse; Cyber security; Serbia; Societal resilience